An Updated Review on Properties, Nanodelivery Systems, and Analytical Methods for the Determination of 5-Fluorouracil in Pharmaceutical and Biological Samples - Dos Santos, Aline Martins [UNESP]; Junior, Alberto Gomes Tavares [UNESP]; Carvalho, Suzana Gonçalves [UNESP]; Chorilli, Marlus [UNESP] (Bentham Science Publishers, 2022)
5-Fluorouracil (5-FU) is an antimetabolite drug used for over 70 years as first-line chemotherapy to treat various types of cancer, such as head, neck, breast, and colorectal cancer. 5-FU acts mainly by inhibiting thymidylate synthase, thereby interfering with deoxyribonucleic acid (DNA) replication or by 5-FU incorporat-ing into DNA, causing damage to the sequence of nucleotides. Being analogous to uracil, 5-FU enters cells using the same transport mechanism, where a is converted into active metabolites such as fluorouridine triphos-phate (FUTP), fluorodeoxyuridine monophosphate (FdUMP), and fluorodeoxyuridine triphosphate (FdUTP). Currently, there are several nano delivery systems being developed and evaluated at the preclinical level to overcome existing limitations to 5-FU chemotherapy, including liposomes, polymeric nanoparticles, polymeric micelles, nanoemulsions, mesoporous silica nanoparticles, and solid lipid nanoparticles. Therefore, it is essen-tial to choose and develop suitable analytical methods for the quantification of 5-FU and its metabolites (5-fluorouridine and 5-fluoro-2-deoxyuridine) in pharmaceutical and biological samples. Among the analytical techniques, chromatographic methods are commonly the most used for the quantification of 5-FU from different matrices. However, other analytical methods have also been developed for the determination of 5-FU, such as electrochemical methods, a sensitive, selective, and precise technique, in addition to having a reduced cost. Here, we first review the physicochemical properties, mechanism of action, and advances in 5-FU nanodelivery systems. Next, we summarize the current progress of other chromatographic methods described to determine 5-FU. Lastly, we discuss the advantages of electrochemical methods for the identification and quantification of 5-FU and its metabolites in pharmaceutical and biological samples.
Keywords: 5-fluorouracil; Analytical methods; chromatographic; electrochemical; mechanisms of action; nanodrug delivery systems; physicochemical properties